The Gospel of Mark: A Hypertextual Commentary - Adamczewski, Bartosz (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2014)
This commentary demonstrates that the Gospel of Mark is a result of a consistent, strictly sequential, hypertextual reworking of the contents of three of Paul's letters: Galatians, First Corinthians and Philippians. Consequently, it shows that the Marcan Jesus narratively embodies the features of God's Son who was revealed in the person, teaching, and course of life of Paul the Apostle. The analysis of the topographic and historical details of the Marcan Gospel reveals that they were mainly borrowed from the Septuagint and from the writings of Flavius Josephus. Other literary motifs were taken